The effect of non-financial compensation on job satisfaction: case study with multiple regression analysis approach at PT. PLN (Persero) WS2JB Palembang Area: NON-FINANCIAL COMPENSATION - Handayani, Susi; Junaidi, Sabda; Nuhaliza, Nuhaliza (Enrichment : Journal of Management, 2024)
In increasingly tight economic conditions, various business ventures are trying to continue to develop and become the best. One of the supporters of achieving company goals is through labor or employees. Employees who master their work will bring employee job satisfaction and provide optimal performance for the company. To encourage employees to work well, one way is through providing compensation both financially and non-financially. This research aims to determine the effect of non-financial compensation on employee job satisfaction at PT. PLN (Persero) WS2JB Palembang Area, with 67 employees used as respondents and the analysis technique used was multiple linear regression. The research results explain that non-financial compensation variables have a significant influence on job satisfaction of 42.9% due to the high level of significance. The research results also support the hypothesis which shows that the author's initial assumption that providing non-financial compensation has an effect on increasing job satisfaction is proven to be correct